A distorção idade-série nos 5º anos do ensino fundamental em uma escola no município de Barcarena - ANJOS, Lucinda Dias dos (2019)
The present work aims to understand the actions mobilized by the management team and by the teachers to solve the problem of the age-series distortion present in the classes of the 5th year of elementary School in the Municipal elementary schools Jarbas Birdie, in Barcarena-Pará. As specific objectives, it is considered: to identify the profile of students with age-series distortion of the 5th year classes; Understand through the perception of school management and teachers which factors have contributed to the occurrence of the age-series distortion; Check whether the school adopts specific program/project for flow correction. The methodology consisted of works by theorists such as Menezes & Santos (2002), Santos (2012), Saviani (2011), Silva (2014), Soares (2015), among others who deal with the theme. The second step was the realization of field research in the aforementioned school, and the population surveyed consisted of one teacher, one coordinator and twelve students. It was possible to identify that one of the factors of DIS is the constant repetition of these students, leading them to age-series distortion, the second is in the fact that many feel difficulties in the learning process. We understand from the teaching conception and school management that the absence of the family in school is a contributing factor for the occurrence of dis. It was found that the school adopts the new more education and more literacy programs as ways to combat dis, the Management team conducts meetings aimed at discussing the problem of distortion, supports and autonomy so that teachers seek to select the content to be worked in the classroom. It was concluded that although the school does not have any specific program for the correction of flow, such as: Brazil advances and accelerates Brazil, the institution is all articulated and committed to combat this situation and seeks to decrease this index in the school.